The Consequences of Cumulative Discrimination: How Special Schooling Influences Employment and Wages of Roma in the Czech Republic - Niall O'Higgins; Christian Brüggemann (Institute for the Study of Labor (IZA), 2013)
Unequal labour market outcomes between Roma and non-Roma have typically been explained by either the low level of educational attainment on the one hand or labour marked discrimination on the other or both. A number of studies have found that significant labour market inequalities persist even after the low levels of educational attainment amongst Roma have been accounted for. Here we look at the role of special schooling in driving labour market inequalities between Roma and non-Roma in the Czech Republic. We confirm the findings of other studies that Roma face significant differences in labour market outcomes which cannot be explained in terms of educational attainment. Moreover, we find that the segregation of Roma into special remedial schools for the mentally disabled influences both labour market outcomes and the level of educational attainment; the latter effect being particularly strong. Special school attendance explains a small part of Roma labour market discrimination as typically measured, but its main impact is through lowering Roma educational attainment suggesting an additional discriminatory element in Roma/non-Roma labour market outcomes which is more typically ascribed to justified Roma/non-Roma educational differences. Thus, we propose that labour market inequality should not only be understood as result of low attainment and labour market discrimination per se but as a complex outcome of cumulative discrimination. In contrast to previous papers which take a parametric approach assuming common support between Roma and non-Roma, the non-parametric matching approach employed here explicitly takes into consideration the substantial differences in educational attainment observable between Roma and non-Roma.
Keywords: J15; I24; 330; Central Europe; labour market discrimination; Roma